Adolescents' exposure to paid alcohol advertising on television and their alcohol use: exploring associations during a 13‐year period. (6th July 2017) - White, Victoria; Azar, Denise; Faulkner, Agatha; Coomber, Kerri; Durkin, Sarah; Livingston, Michael; Chikritzhs, Tanya; Room, Robin; Wakefield, Melanie
Abstract: Aims: To determine (i) whether Australian adolescents' exposure to television alcohol advertisements changed between 1999 and 2011 and (ii) examine the association between television alcohol advertising and adolescent drinking behaviours. Design: Cross‐sectional surveys conducted every 3 years between 1999 and 2011. Analyses examined associations between advertising exposures and reported drinking. Setting: Five Australian major cities. Participants: Students aged 12–17 years participating in a triennial nationally representative school‐based survey residing in the television advertising markets associated with the major cities (sample size range per survey: 12 644–16 004). Measurements: Outcome measures were: drinking in the past month, past week and past‐week risky drinking (5+ drinks on a day). The key predictor variable was past‐month adolescent‐directed alcohol advertising Targeted Rating Points (TRPs, a measure of television advertising exposure). Control measures included student‐level characteristics, government alcohol‐control advertising TRPs, road safety (drink‐driving) TRPs and time of survey. Findings: Average monthly adolescent alcohol TRPs increased between 1999 (mean = 2371) to 2005 (mean = 2679) ( P < 0.01) then decreased between 2005 and 2011: (mean = 880) ( P < 0.01). Multi‐level logistic regression analyses that adjusted for survey timing, student level factors and alcohol‐control advertising variables showed a significant association between past‐month alcohol TRPs and past‐month drinking [odds ratio (OR) = 1.11, 95% confidence interval (CI) = 1.07–1.15), past‐week drinking (OR = 1.10, 95% CI = 1.06–1.14) and past‐week risky drinking (OR = 1.15, 95% CI = 1.09–1.22). Past‐week risky drinking was associated inversely with road safety TRPs (OR = 0.69, 95% CI = 0.49–0.98). Conclusions: While Australian adolescents' exposure to alcohol advertising on television reduced between 1999 and 2011, higher levels of past‐month television alcohol advertising were associated with an increased likelihood of adolescents' drinking. The reduction in television alcohol advertising in Australia in the late 2000s may have played a part in reducing adolescents' drinking prevalence.